2014
DOI: 10.1073/pnas.1317660111
|View full text |Cite
|
Sign up to set email alerts
|

Ability of preventive therapy to cure latent Mycobacterium tuberculosis infection in HIV-infected individuals in high-burden settings

Abstract: Trials of isoniazid preventive therapy (IPT) for people living with HIV in southern Africa have shown high rates of tuberculosis disease immediately after cessation of therapy. This could be due to the lack of cure following preventive therapy or reinfection with rapid progression to disease. Using a model fitted to trial data, we estimate the degree to which preventive therapies cure latent Mycobacterium tuberculosis infection in HIV-infected individuals in high-tuberculosis-burden settings. We identified ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
2
40
0
1
Order By: Relevance
“…In contrast, in a previous analysis of trial data from the pre-antiretroviral therapy (ART) era, we found that the high rates of TB following completion of 6-12 months IPT in PLHIV were consistent with an almost complete lack of 'cure' of latent Mycobacterium tuberculosis infection (LTBI) [8]. Mathematical modelling of a trial of community-wide INH in South African gold mines reached similar conclusions about the effectiveness of IPT in PLHIV [9].…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…In contrast, in a previous analysis of trial data from the pre-antiretroviral therapy (ART) era, we found that the high rates of TB following completion of 6-12 months IPT in PLHIV were consistent with an almost complete lack of 'cure' of latent Mycobacterium tuberculosis infection (LTBI) [8]. Mathematical modelling of a trial of community-wide INH in South African gold mines reached similar conclusions about the effectiveness of IPT in PLHIV [9].…”
Section: Introductionmentioning
confidence: 50%
“…The model is based on a previously published model [8] and is similar in structure to a number of other TB models [16,17]. It describes the TB dynamics in a preventive therapy trial cohort of HIV-infected individuals on ART after the cessation of IPTor placebo.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions [9], studies of LTBI susceptibility and genetic variation occurred in tuberculosisendemic regions (geographic differences may affect responses to tuberculosis treatments) [28,29] and did not adjust for epidemiologic risk factors, potentially leading to loss of study power. We enrolled close contacts of tuberculosis cases through a US tuberculosis program to examine whether variation in autophagy genes is associated with susceptibility to M. tuberculosis infection.…”
mentioning
confidence: 99%
“…B. auf 36 Monate) die Wirksamkeit erhöht, allerdings erlischt die protektive Wirkung oft, sobald die Gabe von INH abgebrochen wird[57]. In einer Modellanalyse ist dargestellt worden, dass INH bei koinfizierten Personen die LTBI nicht ausheilen kann und auch aufgrund des Risikos einer Reinfektion eine kontinuierliche Gabe nötig ist[58]. Die subklinische TB-Erkrankung und die Häufigkeit einer Reinfektion als Ursache für ein TB-Rezidiv fordern dazu auf, die Konzepte der LTBI-Behandlung zu überdenken[50].…”
unclassified